Dari Sains Fiksi ke Medan Perang: Realitas dan Tantangan Pesawat Tanpa Awak Bersenjata dengan Kecerdasan Buatan - Santosa Edy Wibowo (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
The integration of artificial intelligence (AI) into Unmanned Aerial Vehicles (UAVs) has revolutionized modern warfare, offering significant strategic advantages while simultaneously raising profound ethical and regulatory challenges. This journal explores the multifaceted implications of AI-weaponized UAVs, examining their strategic benefits, ethical concerns, regulatory needs, and potential future applications. It argues for a cautious approach to development and deployment, emphasizing the crucial need for international cooperation and ethical frameworks to mitigate the risks associated with this transformative technology.